Leading During A Public Health Crisis - Angela Sheedy; Dianne Stephens; Lisa Vermeulen (Asia Pacific Journal of Health Management)
Leading teams during the COVID-19 pandemic had unique challenges often requiring timely decisions based on emerging new information to then rapidly implement changes. The usual scaffolding for system changes lagged behind the implementation. The command and control of crisis management blended with traditional health leadership styles as the emergency response became protracted and building sustainable teams became a focus of the response.